Effect of brining on the drying rate of tilapia (Oreochromis niloticus) in a solar tunnel dryer - Kituu, G.M; Shitanda, Douglas; Silayo, V.; Odote, Peter; Bongyereire, J (Acta Press, 2008)
This study determined effect of on the drying rate of tilapia in a solar tunnel dryer. Tilapia fish was split into pieces of 4cm by 3cm by 9mm and soaked into four brine concentrations varying between 0-15%. Moisture content was evaluated by oven drying method, while air temperatures were with an automated data logger. The moisture content of fish reduced as brine concentration increased. The effective diffusion coefficient varied between 5.061 *10-11and 3.323*10-11 m2/s as brine concentration increased, and it decreased with increase in brine concentration
Keywords: Solar; Tunnel dryer; Brining; Diffusivity; Moisture content